Etiology and Pathophysiology of Hypoparathyroidism: A Narrative Review. (23rd November 2022) - Pasieka, Janice L.; Wentworth, Kelly; Yeo, Caitlin T.; Cremers, Serge; Dempster, David; Fukumoto, Seiji; Goswami, Ravinder; Houillier, Pascal; Levine, Michael A.; Pasternak, Jesse D.; Perrier, Nancy D.; Sitges‐Serra, Antonio; et al.
ABSTRACT: The approach utilized a systematic review of the medical literature executed with specifically designed criteria that focused on the etiologies and pathogenesis of hypoparathyroidism. Enhanced attention by endocrine surgeons to new knowledge about parathyroid gland viability are reviewed along with the role of intraoperative parathyroid hormone (ioPTH) monitoring during and after neck surgery. Nonsurgical etiologies account for a significant proportion of cases of hypoparathyroidism ( 25%), and among them, genetic etiologies are key. Given the pervasive nature of PTH deficiency across multiple organ systems, a detailed review of the skeletal, renal, neuromuscular, and ocular complications is provided. The burden of illness on affected patients and their caregivers contributes to reduced quality of life and social costs for this chronic endocrinopathy. © 2022 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).